2012
DOI: 10.1073/pnas.1121534109
|View full text |Cite
|
Sign up to set email alerts
|

IL-38 binds to the IL-36 receptor and has biological effects on immune cells similar to IL-36 receptor antagonist

Abstract: The functional role of IL-1 family member 10, recently renamed IL-38, remains unknown. In the present study we aimed to elucidate the biological function of IL-38 and to identify its receptor. Heatkilled Candida albicans was used to stimulate memory T-lymphocyte cytokine production in freshly obtained human peripheral blood mononuclear cells from healthy subjects. The addition of recombinant IL-38 (152 amino acids) inhibited the production of T-cell cytokines IL-22 (37% decrease) and IL-17 (39% decrease). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
329
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(354 citation statements)
references
References 35 publications
12
329
0
3
Order By: Relevance
“…The immune effects of IL-36a seem to be antagonized by two different IL-36R ligands, IL-36RA and IL-38. Ligation of IL-36RA and/or of IL-38 with the IL-36R may, in fact, reverse the proinflammatory properties of IL-36a [21].…”
Section: Discussionmentioning
confidence: 99%
“…The immune effects of IL-36a seem to be antagonized by two different IL-36R ligands, IL-36RA and IL-38. Ligation of IL-36RA and/or of IL-38 with the IL-36R may, in fact, reverse the proinflammatory properties of IL-36a [21].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in vitro, IL-38 inhibits the production of Th1 cytokines, IL-17, and IL-22. IL-38, similarly to IL-36Ra, has an anti-inflammatory effect on PBMCs, contrasting with a clearly pro-inflammatory effect on DC with increased IL-6 production [45]. IL-38 is selectively secreted by human apoptotic cells to counteract inflammation.…”
Section: Il-36 and Il-38mentioning
confidence: 99%
“…During the past several years many papers have described a key role for IL-36 in psoriasis which is overexpressed in the skin of human plaque psoriasis (17)(18)(19). The inhibition of IL-36 with IL-36RA in human psoriatic skin has been found to ameliorate the inflammatory reactions (20)(21)(22)(23). It has been shown that IL-22, IL-17A, and TNF-a induce the ex vivo production of all three IL-36 by human keratinocytes, whereas IFN-y selectively induces IL-36P (24-26).…”
Section: Inhibits the Production Of Ifn-y Il-4 And Il-17 By Cd4(+) mentioning
confidence: 99%